Correlation of Levels Indonesian Language Skill In Using Indonesian Sentence Structure With Achievement Motivation On Student Learning Outcomes SMP 2 Satap Pangkatan Labuhan Batu - Rahmaidani Siregar; Sutikno; Rahmat Kartolo (PT Inovasi Pratama Internasional, 2026)
The research problem in this study is: What is the correlation between the level of proficiency in using Indonesian sentence structures and achievement motivation on the learning outcomes of Grade VIII students at SMP Negeri 2 Satap Pangkatan, Labuhan Batu Regency, in the academic year 2025-2026? The purpose of this study is to determine the correlation between the level of proficiency in using Indonesian sentence structures and achievement motivation on the learning outcomes of Grade VIII students at SMP Negeri 2 Satap Pangkatan, Labuhan Batu Regency, in the academic year 2025-2026. This study employs a descriptive method with a correlation analysis technique. The population of this research includes all Grade VIII students of SMP Negeri 2 Satap Pangkatan in the academic year 2025-2026, totaling 60 students. The sample was taken as a total sampling (population study). The research instruments used were tests and questionnaires. Tests were employed to measure the proficiency in using Indonesian sentence structures and writing expository texts, while questionnaires were used to collect data on students' achievement motivation. The results of the study show a significant relationship between proficiency in using Indonesian sentence structures and achievement motivation on students' learning outcomes. At a 5% significance level, the ttt-test value exceeds the ttt-table value, thus accepting the hypothesis HaH_aHa. Therefore, proficiency in using Indonesian sentence structures has a positive correlation with expository writing skills, as does achievement motivation, which contributes to the learning outcomes of expository writing for Grade VIII students at SMP Negeri 2 Satap Pangkatan, Labuhan Batu Regency, in the academic year 2025-2026